Meeting Diverse Learner Needs: Perception and Practices of Differentiated Instruction - Agustina, Imas Wahyu; Palupi, Tara Mustikaning; Sari, Sulhizah Wulan (Universitas Negeri Makassar, 2025)
Abstract. As Indonesian students bring a wide range of cultures, beliefs, needs, interests, and attitudes into their English class, differentiated instruction (DI) can offer a possible yet challenging solution since it enables learning to fit the students' needs but opposes the standardized one-size-fits-all education model. This study investigated the teachers' perception of differentiated instruction in English language learning and its implementation. This study employs a descriptive qualitative design using questionnaires adapted from Tomlinson’s (2017) concept of differentiating learning elements based on learners’ variances to collect data from 48 junior and senior high school English teachers in the Jabodetabek area. The findings revealed that respondent teachers were generally aware that DI required teachers to adjust the learning to the students’ needs, yet only a few fully noticed that modification was conducted in the content, process, and product according to the readiness, interest, and profile. They implemented various DI strategies by varying the resources, complexity, titles, situations, structures, supports, output formats, working procedures, and deadlines. However, concerns about the implementation remain due to the excessive demands for effort and time for preparation, highlighting the need for ongoing, context-specific professional support. This study hopefully brings insights to help all English teachers with the practices of DI in their classes and raises awareness of the importance of DI to allow all language learners to achieve similar learning outcomes despite their individual differences. Keywords: Differentiated Instruction; Differentiated Instruction Strategies: Implementation of Differentiated Instruction; Teacher's Perception of Differentiated Instruction